Early Childhood Education and the Role of Nursery School Teacher, Medellín-Colombia: 1915-1930 (2018)
This paper analyzes the historical production of a kind of school knowledge that enabled the education of preschoolers and the formation of the preschool or nursery school teacher at Colegio María Auxiliadora of Medellin, by means of the appropriation of Pestalozzi, Fröebel and Montessori methods. Methodologically, this pedagogical practice was studied from a historical approach; additionally, some archeogenealogical tools were used. The contents of the text are developed in three moments: the irst analyzes the emergence of the nursery school teacher, the second examines the institutionalization of early childhood teaching as the irst instructional level, and a third moment rewrites the discourses and practices of early childhood education and preschool teacher training. The indings include the power-knowledge tensions that occurred in the context of catholic pedagogy, a characterization of the knowledge considered necessary for the education of preschoolers, and the coniguration of the Early Childhood Pedagogy Program for the training of preschool teachers. In conclusion, some uses of the educational experience of the present Salesian kindergarten are related, recurring to the notion of active memory of pedagogical knowledge, that will allow the future reconceptualization of early education.